PDRAM: a hybrid PRAM and DRAM main memory system - Dhiman, Gaurav; Ayoub, Raid; Rosing, Tajana (2009 46th ACM/IEEE Design Automation Conference, 2009)
In this paper, we propose PDRAM, a novel energy efficient main memory architecture based on phase change random access memory (PRAM) and DRAM. The paper explores the challenges involved in incorporating PRAM into the main memory hierarchy of computing systems, and proposes a low overhead hybrid hardware-software solution for managing it. Our experimental results indicate that our solution is able to achieve average energy savings of 30% at negligible overhead over conventional memory architectures.